Effects of EGFR Inhibitors on Proton Pump Function in Gastric Mucosa and Its Mechanism - Wu, Rongxiang (International Journal of Public Health and Medical Research, 2024)
This research was carried out to detect the influence of the proton pump mechanism function on the EGFR inhibitor. Human gastric cancer cell line MKN-45 cells were divided into different concentrations of EGFR inhibitors and treated with either AG1478 or PD153035. Western Blot and immunofluorescence describe the expression of proton pump (H+/K+ ATPase). Next, the phosphorylated levels of ERK and AKT were analyzed. The overall disruption and strong results in the effects of EGFR inhibition, proton-pump transcription, and phosphorylation of ERK and AKT indicated the vital importance of this pathway. Moreover, this study also indicated that EGFR inhibitors were inhibitors of the EGFR signaling pathways themselves due to a decrease in the expression and activity of the proton pump; moreover, this inhibitory effect was closely related to drug concentration. Such findings open up new treatment opportunities for various gastric diseases and underline the possibly critical role of EGFR in gastric acid regulation.